An Approach for Self-Adaptive Path Loss Modelling for Positioning in Underground Environments - Evgeny Osipov; Denis Kleyko; Alexey Shapin (International Journal of Antennas and Propagation)
This paper proposes a real-time self-adaptive approach for accurate path loss estimation in underground mines or tunnels based on signal strength measurements from heterogeneous radio communication technologies. The proposed model features simplicity of implementation. The methodology is validated in simulations and verified by measurements taken in real environments. The proposed method leverages accuracy of positioning matching the existing approaches while requiring smaller engineering efforts.